DsbM affects aminoglycoside resistance in Pseudomonas aeruginosa by the reduction of OxyR. Issue 2 (24th February 2014) - Li, Mingxuan; Guan, Xinyu; Wang, Xuehan; Xu, Haijin; Bai, Yanling; Zhang, Xiuming; Qiao, Mingqiang
Abstract DsbM is a novel disulfide oxidoreductase that affects aminoglycoside resistance in Pseudomonas aeruginosa by an OxyR‐regulated process. However, the detailed mechanism of interaction between DsbM and OxyR had not yet been elucidated. In this study, we expressed DsbM in Escherichia coli and showed that DsbM can oxidize and reduce disulfide. We also used a yeast two‐hybrid assay to identify interactions between DsbM and OxyR. A subsequent GSH oxidation experiment revealed that DsbM could alter both the oxidized and reduced state of OxyR. We hypothesized that OxyR can be reduced by DsbM, and thus DsbM may be required for aminoglycoside resistance in P. aeruginosa. Our findings contribute to the understanding of the mechanisms underlying aminoglycoside resistance in P. aeruginosa.